The Effectiveness of Web Based Student Services at the Faculty of Islamic Education and Teaching - Firnando, Aditiya; Hasbi, Muhammad; Sri Eva Mislawati (The Future of Education Journal, 2026)
This study aims to analyze the effectiveness of web-based student services (SILAYAK) at the Faculty of Tarbiyah and Teacher Training, UIN Raden Fatah Palembang, and to identify the supporting and inhibiting factors in its implementation. SILAYAK is an academic service innovation that is effective in improving the quality of student services. This research uses a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The key informants were the Head of Administration and the SILAYAK administrator, while the supporting informants were students of the Islamic Education Management study program. The results show that the web-based student service system (SILAYAK) has been implemented quite effectively based on the five service quality indicators (SERVQUAL), namely reliability, assurance, tangibles, empathy, and responsiveness. The system provides easy access to academic services online, improves time efficiency, and simplifies student administrative processes. However, several obstacles remain, particularly related to internet network issues and technical disruptions that hinder optimal service performance. Supporting factors for service effectiveness include the availability of digital-based systems, ease of access to information, and the readiness of human resources in operating the system. Meanwhile, inhibiting factors include dependence on internet connectivity, potential system errors, and limited user understanding of application procedures. Therefore, improvements in technical aspects and infrastructure are needed to ensure optimal performance.